The effect of depth of cure on microhardness between bulk-fill and hybrid composite resin material - Ahmed A. Elhejazi; Asim Alosimi; Faisal Alarifi; Abdullah almuqayrin (Elsevier, 2024)
Background: Functional properties should be considered when selecting composites for restorations. With bulk-fill resin composites, the disadvantages of conventional composites were overcome regarding the increments necessitating the application of a 2 mm thick layer of resin and the amount of polymerization. The most significant advantage of bulk-fill resin composite is the possibility of applying the material in 4 mm layers. Multiple studies have examined the polymerization, mechanical, and adhesive properties of bulk-fill resin composites and proven them successful. Objective: This study aimed to compare the effect of the depth of cure on the microhardness between different bulk-fill composites and a hybrid composite material by following the manufacturer's instructions. Methods: In this in vitro study, five composite types obtained from different companies were used: two high-viscosity bulk-fill composites, Filtek and OPUS bulk; two low-viscosity bulk-fill flowable composites, Any-com and OPUS flow; one light-cure hybrid composite, Cavex, totaling 25 samples. The composite was applied at a depth of 4 mm in the bulk-fill composite and 2 mm in the hybrid composite and light-cured. The microhardness was measured at three different times. The first time was performed immediately after light-curing, the second time was evaluated 24 h after polymerization, and the third time was after thermocycling. Result: A total of 25 samples showed that the microhardness increased the first and second times and decreased the third time after thermocycling on the top and bottom sides of Filtek, OPUS bulk-fill, OPUS flow, and Any-com bulk. The Cavex microhardness at the bottom was equal at all three-time points. Two-way repeated measures ANOVA showed that the microhardness between all types of composite resin materials was significantly different at different times when p = 0.00.